Polysplenia Syndrome Associated With Heterotaxy of Abdominal Viscera and Type IV Intestinal Atresias - Safwan Ahmad (EL-Med-Pub, 2012)
Polysplenia syndrome in association with situs inversus and intestinal atresia is rarely reported [1]. A 2-day-old male neonate was presented with neonatal intestinal obstruction. Abdominal radiograph showed air fluid levels suggestive of small bowel atresia. Ultrasound of the abdomen showed dilated bowel loops throughout the abdominal cavity. At operation, there was right sided stomach, centrally located liver, three spleens at normal location, and type IV small bowel atresias. All the small bowel atresias were resected and end to end jejuno-ileal anastomosis was performed. One of the spleens which had a narrow pedicle was removed to prevent any future torsion. The postoperative course remained stormy and patient succumbed to sepsis on 5th postoperative day.